KOMPRES KUBIS DAN SIRIH MERAH EFEKTIF MENURUNKAN DERAJAT PEMBENGKAKAN PAYUDARA IBU POSTPARTUM - Siti Rofi'ah; Istu Putri Rahayu; Nuril Nikmawati (Badan Perencanaan Pembangunan Daerah Kota Magelang, 2020)
As a mother will certainly give all the best, including exclusive breastfeeding for her beloved baby. One of the failures in breastfeeding is due to breast swelling. Cabbage leaves contain sinigrin (allylisothiocyanate) rapine, mustardoil, magnesium, oxylate, sulfur. A red betel leaf contains flavonoids, polevenolad, tannins, and essential oils. Empirically these substances have the effect of disappearing pain and swelling. The purpose of this study was to determine the effectiveness of cabbage and red betel leaf compresses on the degree of postpartum breast swelling.The research method is quasy experimental study with pretest-posttest with control group design. The study population was mothers who gave birth in March to April 2019 in the working area of Mungkid Magelang Public Health Center with a total of 45 respondents. Respondents were divided into 3 groups: 15 postpartum mothers with cabbage compress intervention group, 15 postpartum mothers with red betel leaf compress intervention group and 15 postpartum mothers with control group. The sampling technique is total sampling. Analyze using the Wilcoxon statistical test.Theresults showed that there were any differences in the scale of swelling before and after the intervention in the experiment and control groups. Cabbage compress with <p = 0.001, Red Betel Leaf Compress with p = 0.014 and Control Group with p = 0.025. Cabbage compress is the most effective in reducing the degree of postpartum breast swelling. It is recommended that postpartum mothers with breast swelling can apply cabbage compress as one of the technique to reduce the degree of breast swelling. For health workers, especially midwives are expected to teach cabbage compress techniques to postpartum mothers as one of the non-pharmacological therapies to reduce the degree of postpartum breast swelling.